The Effectiveness of the Occupational Health and Safety Management System at PT. PLN (Persero) - Darwis, Muh; Muchlisa, Dhiya; Siagian, Ade Onny (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This research is a quantitative descriptive study that aims to determine the level of effectiveness of the Occupational Health and Safety Management System at PT. PLN (Persero) Main Unit for South, Southeast, West Sulawesi (Sulselrabar). The population of this study is 45 respondents and was gathered using saturated sampling. The data collection techniques used were observation, questionnaires, interviews, and documentation. The data analysis technique used is the percentage analysis and descriptive distribution. The results showed that the occupational safety and health management system is classified as ’very effective’, using indicators such as OSH policy determination, OHS planning, implementation of OHS plans, monitoring and evaluation of Occupational Health and Safety performance. To achieve the effectiveness of the Occupational Health and Safety Management System, efforts are made to achieve company goals, namely running an electricity business, oriented to customer satisfaction, making electricity a medium to improve the quality of people’s lives, and striving for electricity to be a driving force for activities.